Internet Addiction and Depression in Chinese Adolescents: A Moderated Mediation Model - Chi, Xinli; Liu, Xiaofeng; Guo, Tianyou; Wu, Mingxia; Chen, Xiaochen (Frontiers in Psychiatry, 2019)
Research has revealed that Internet addiction is a risk factor for adolescents’ development of depressive symptoms, although the underlying mechanisms are largely unknown. The present study examines the mediating role of positive youth development and the moderating role of mindfulness to determine the association between Internet addiction and depression. A sample of 522 Chinese adolescents completed measures related to Internet addiction, positive youth development, mindfulness, depression, and their background information, for which the results reveal that positive youth development mediates the relation between Internet addiction and depression. Moreover, the associations between both Internet addiction and depression as well as positive youth development and depression are moderated by mindfulness. These two effects were stronger for adolescents with low mindfulness than for those with high mindfulness. The present study contributes to a more thorough understanding of how and when Internet addiction increases the risk of depression in adolescents, suggesting that Internet addiction may affect adolescent depression through positive youth development and that mindfulness can alleviate the negative effect of Internet addiction or a low level of psychological resources on depression. The implications for research and practice are finally discussed.